Evaluación de Susceptibilidad a Movimientos de masa en la loma "San Vicente" en el cantón Otavalo-provincia de Imbabura, en el período abril – septiembre 2023 - Rodríguez Tituaña, Denis Solange (2023)
The objective of this research work is to evaluate the susceptibility of mass movements of the San Vicente hill located north east of the city of Otavalo; in order to create strategies to minimize these mass movements, by identifying the triggering and conditioning factors that the territory has, to protect living beings, material goods, vital networks and essential elements of the territory. The research has a non-experimental design, as it does not manipulate the variables of the Mora-Vahrson methodology, which allows a prior analysis of areas threatened by landslides, morphodynamic indicators were used such as: relative relief, lithology, soil humidity, seismic activity and precipitation. This is specified by influence indices that are worked on in the Geographic Information System (GIS), where maps were created with the triggering and conditioning parameters. Using the raster calculator tool of the spatial analysis method called map algebra, the map is created. of susceptibility to mass movements as a final result. Modeling was carried out using the geotechnical software GEO 5, to determine the stability of the slope, which describes whether the capacity of the terrain will be able to resist the action of the forces that can cause a collapse. Finally, strategies are formed following the risk management areas to minimize susceptibility to mass movement on the “San Vicente” hill, detailed through a matrix according to the level of vulnerability of the territory.